Impact of pre‐procedural hyponatremia on clinical outcomes after transcatheter aortic valve replacement: A propensity‐matched analysis. Issue 2 (11th January 2018) - Kagase, Ai; Yamamoto, Masanori; Shimura, Tetsuro; Kodama, Atsuko; Kano, Seiji; Koyama, Yutaka; Tada, Norio; Naganuma, Toru; Araki, Motoharu; Yamanaka, Futoshi; Shirai, Shinichi; Watanabe, Yusuke; et al.
Abstract: Background: Hyponatremia is associated with the increased risk of early and late mortality in patients with cardiac disease. This study aimed to assess the prognostic value of hyponatremia in patients who had undergone transcatheter aortic valve replacement (TAVR). Methods: We investigated 1, 215 consecutive patients (mean age: 84.4 ± 5.0 years) who underwent TAVR using data from the Optimized CathEter vAlvular iNtervention (OCEAN)‐TAVR Japanese multicenter registry. Hyponatremia was defined as a serum sodium value less than 135 mEq/L. The baseline characteristics, procedural outcomes, all‐cause, cardiovascular, and non‐cardiovascular mortality were compared between patients with hyponatremia ( n  = 106, 8.7%) and without hyponatremia ( n  = 1, 109, 91.3%). A propensity‐matching analysis was used to adjust for the non‐uniform patient characteristics. Results: Differences in the baseline characteristics were observed between the two groups regarding the prevalence of pulmonary disease (37.7% vs. 28.9%, P  = 0.04) and the performance of non‐elective TAVR (10.4% vs. 4.2%, P  = 0.01), although these were minimized in the matched model. The 30‐day mortality rates differed between the two groups (7.6% vs. 1.4%, P  < 0.001). During a mean follow‐up of 330 days, the all‐cause and cardiovascular mid‐term mortality were higher in the hyponatremia group than in the non‐hyponatremia group (log‐rank test: P  = 0.0047, and P  < 0.001, respectively). The three findings above were not attenuated in the propensity‐matched model ( P  < 0.001, P  = 0.0044, and P  = 0.014, respectively). In contrast, there was no difference in non‐cardiovascular mortality between the two groups in both the overall and matched model ( P  = 0.40 and P  = 0.13, respectively). Conclusions: Pre‐procedural hyponatremia may be a useful marker for predicting early and mid‐term clinical outcomes after TAVR.